La internacionalización de las empresas exportadoras. Estado de la cuestión (2016)
Globalization is a process that has been given to the global level and for Colombia this is no stranger; through the “Vision 2032” it is proposed that our country will become one of the three most competitive countries in Latin America, thus Bucaramanga and its metropolitan area, take on this challenge as a fundamental axis for the economic and social development of the country and the region, increasing the participation of firms in global markets. This article makes a theoretical review of the internationalization and the exporting companies, to find the fundamental aspects that make it possible to establish the influence of the competitiveness and technological capital in the internationalization of the exporting companies and also constitute a source of query from the academic and business, contribution to decisions in the internationalization of companies in the region.